The Use of a Bee-bot in Pre-primary and Primary Education - Vargová, Mária; Círus, Lukáš (Journal of Education, Technology and Computer Science, 2021)
Modern teaching aids are part of the daily education process. Children, pupils use them to deepen the acquired knowledge. A teacher tries to alternate the teaching methods in an interesting way. The Bee-bot, a didactic toy, has been used in education for several years. The teacher decides at what intervals and in which subject he or she can use the Bee-bot. In this article we present one of a group of micro-outputs. Here we used a heuristic method, a method of discovery and observation. Also, we used the cooperation in the application of a robotic toy.